Dynamics of Border Community Business: A Case Study of Bengkayang Regency, West Kalimantan - Beni, Sabinus; Atlantika, Yeremia Niaga; Salfarini, Eligia Monixa; Manggu, Blasius (International Journal of Multi Discipline Science (IJ-MDS), 2024)
This research is motivated by the complexity of business dynamics among communities in the border region of Bengkayang Regency. Border regions have unique characteristics, leading to various factors influencing business dynamics in these areas. This research aims to understand the business dynamics of communities in the border region of Bengkayang Regency and formulate strategies for their development. This study employed a qualitative approach using a case study method. Data was collected through in-depth interviews, participant observation, and documentation. The data analysis technique used was narrative analysis to deeply understand the experiences of business actors. The results showed that the business dynamics of communities in the border region of Bengkayang Regency are influenced by various factors, such as government policies, ethnicity, border security, infrastructure, skills and knowledge, and government roles. Based on the research findings, several strategies for business development in the border region of Bengkayang Regency were formulated, including infrastructure improvement, provision of training and business mentoring, facilitation of partnerships with large-scale businesses, enhancement of border security, and strengthening cross-border cooperation.